Factors that influence commuters' willingness to ride on public transport in Malaysia - Ng, Qiu Yuan Bernice (2019)
This research in this review focused on the factors that influence the willingness to ride on public transport. It provides empirical evidence that time, comfort and safety are three key components contributing to the decision making on the viability of alternatives transportation modes. One of the biggest challenges encountered in Malaysia is the increasing number of private vehicles on the road which will lead to further problems such as acute traffic congestion, emissions of excessive carbon dioxide (CO2), and fatality cases. The encouragement of the ridership of public transport could be the best alternative to reduce the on-the-road vehicles. However, it is difficult to stimulate the willingness to ride on public transport without a clear understanding of people’s travel behavior towards developing a seamless public transport system. This study sought to identify and study the importance of these factors and how are they correlated with each other to influence the willingness to ride. Primary data from 230 respondents with profession mixture of student, employee, employer, self-employed, unemployed and retiree are collected by undergoing a quantitative research of questionnaire. Descriptive, exploratory factor analysis, multiple regression analysis and PROCESS are used to test the hypotheses corresponding to the research objectives for this study. The result indicated that time has a significant relationship with safety and comfort. In a meanwhile, safety has also shown to have positive influence on comfort. The direct relationship of safety and comfort on willingness to ride on public transport has been supported with literature reviews to discuss further. In order to develop a sustainable public transport system in Malaysia, it is prominent to increase the awareness for people on the beneficial of riding public transport and to achieve to provide access to safe, affordable, accessible and sustainable transport system for everyone.